Diabetes Self-Care and Quality of Life Improvement Through Community Self-Help Group - Zaroan Supriadi; Kumboyono Kumboyono; Dina Dewi Sartika Lestari Ismail; Niko Dima Kristianingrum; Yati Sri Hayati; Annisa Wuri Kartika (Poltekkes Kemenkes Surakarta, 2025)
Background: Type 2 diabetes mellitus (T2DM) remains a major cause of death worldwide due to complications, and its incidence is fairly high and predicted to continue to rise each year. This contributes to a low quality of life and poor self-care management, necessitating an effective treatment strategy consisting of self-help group (SHG) therapy that expands social networks, receives information, and receives emotional support from group members in order to provide numerous benefits. The purpose of this study was to assess if community-based self-help group interventions improve the quality of life and self-care management of individuals with T2DM. Methods: This study employed a Quasi-experiment non-equivalent control group pre-test and post-test design with a self-help group intervention (n=30) for one month. The sample was selected using the approach of purposive selection with the following inclusion criteria: age between 40 and 65 years, T2DM experience between 3 and 5 years, and the ability to converse, read, and write effectively. Statistical paired sample t-test and independent sample t-test were used to assess the data. Results: In both groups, self-care management, quality of life, and blood glucose levels at baseline were comparable. After one month of intervention, self-care management, quality of life, and blood glucose levels were significantly better in the intervention group than in the control group (p<0.05). Conclusion: In this study, the self-care management and quality of life of individuals with T2DM improved following SHG intervention. Integrating public health effort with an interpersonal collaboration approach will provide an optimal integrated contribution to resolving chronic deseases.